Pavlovian Conditioning of Larval Drosophila: An Illustrated, Multilingual, Hands-On Manual for Odor-Taste Associative Learning in Maggots - Michels, Birgit; Saumweber, Timo; Biernacki, Roland; Thum, Jeanette; Glasgow, Rupert D. V.; Schleyer, Michael; Chen, Yi-chun; Eschbach, Claire; Stocker, Reinhard F.; Toshima, Naoko; Tanimura, Teiichi; Louis, Matthieu; et al. (Frontiers in Behavioral Neuroscience, 2017)
Larval Drosophila offer a study case for behavioral neurogenetics that is simple enough to be experimentally tractable, yet complex enough to be worth the effort. We provide a detailed, hands-on manual for Pavlovian odor-reward learning in these animals. Given the versatility of Drosophila for genetic analyses, combined with the evolutionarily shared genetic heritage with humans, the paradigm has utility not only in behavioral neurogenetics and experimental psychology, but for translational biomedicine as well. Together with the upcoming total synaptic connectome of the Drosophila nervous system and the possibilities of single-cell-specific transgene expression, it offers enticing opportunities for research. Indeed, the paradigm has already been adopted by a number of labs and is robust enough to be used for teaching in classroom settings. This has given rise to a demand for a detailed, hands-on manual directed at newcomers and/or at laboratory novices, and this is what we here provide. The paradigm and the present manual have a unique set of features: • the paradigm is cheap, easy, and robust; • the manual is detailed enough for newcomers or laboratory novices; • it briefly covers the essential scientific context; • it includes sheets for scoring, data analysis, and display; • it is multilingual: in addition to an English version we provide German, French, Japanese, and Spanish language versions as well. The present manual can thus foster science education at an earlier age and enable research by a broader community than has been the case to date.